Methodology to estimate the total sediment transport in mountainous river basins - Jacinto Artigas; José Luis López; José Rafael Córdova (Revista Técnica de la Facultad de Ingeniería, 2010)
The determination of the sediment yield in mountain basins is an important task in water resources management, and also in the design of hydraulic works. The estimates of sediment yield are usually obtained by considering mainly the suspended sediment, neglecting or assigning a proportion to the material that is transported as bed load. The paper's objective is the development of a methodology to estimate the total sediment yield (suspended and bed loads) in mountain streams. Watershed laminar erosion is computed by using the MUSLE model, in order to estimate suspended sediment load. Bed load is calculated by applying the equations of Schoklitsh and Meyer-Peter/Müller. These models are applied using extraordinary events hydrographs, associated with storms of 10, 25, 50 100 and 500 years of return period, in order to obtain a functional relationship between the sediment yield due to laminar erosion and bed load. This relationship allows the estimation of monthly and annual series of total sediment yield, by using a continuous rainfall-runoff model. The methodology is applied on several watersheds located on the Southern slope of El ívila National Park, in Caracas, Venezuela.